The city of dreaming books : a novel from Zamonia - Moers, Walter, 1957- (Overlook Press, 2008)
Optimus Yarnspinner inherits a manuscript by an unknown writer. To track down the author, he goes to Bookholm, the City of Dreaming Books, where book-related attractions abound.